(3JMOjO GdGMJjGLGJ GdJOQjHjIs - (3GdSjO(B, (3YdjhIs ((3GdbGgQI(B:s (3GjJQGc ddfTQ h GdJhRjY(B,s, 2001)
(3eaGgje hCSGSjGJ GdJOQjH , JMOjO GdEMJjGLGJ GdJOQjHjI , JNWjW fXGe GdJOQjH , GdXQha GdeDKQI Ydi YbO GdHQfGeL GdJOQjHj , CSGdjH GdJOQjH GNJjGQ hJfXje gjFI GdJOQjH , eJGHYI Jbje fTGW GdJOQjHs
(3HjHdjhZQGajG (B: (3U(B.181s
Keywords: (3GdJOQjH Gdegfi(B-(3eUQs; (3JfXjes